Facebook's Presupposition “Rizky Billar Had Said He Wanted to Retire from the Entertainment World” - Fazry Suci Hasibuan; Yusni Khairul Amri (Britain International for Academic Research (BIAR-Publisher), 2022)
This data is entitled Facebook's Presupposition “Rizky Billar Had Said He Wanted to Retire from the Entertainment World”. This research is an attempt to identify and analyze the types and meanings of presuppositions on Facebook. The data used in this study are in the form of comments on Facebook. The data are analyzed using the following steps. (1) Read comments on Facebook social media, (2) Mark each word or sentence that contains a form of presupposition, (3) Classify based on the types of presuppositions, (4) Summarize the data that has been presented carefully. Facebook data contains comments as many as 24 comments. In this research, the author uses a descriptive method that analyzes based on the theory of George Yule (1996) there are six types of presuppositions. The results of the study concluded that there are six types of presuppositions in Facebook social media, namely: existential presuppositions, active presuppositions, lexical presuppositions, structural presuppositions, inactive presuppositions, and counteractive presuppositions.